Association between income and likelihood of right heart catheterization in individuals with pulmonary hypertension: A US claims database analysis - Erin M. Schikowski; Gretchen Swabe; Stephen Y. Chan; Jared W. Magnani (Pulmonary Circulation, 2022)
Abstract We used a US‐based administrative claims database to determine associations between annual household income and the likelihood of right heart catheterization (RHC) among individuals with pulmonary hypertension. Those with annual household income < $40,000 were 19% less likely to receive RHC compared to individuals with annual household income ≥ $100,000 (p < 0.0001).